Alpha-Glucosidase and Alpha-Amylase Inhibitory Activities, Molecular Docking, and Antioxidant Capacities of Salvia aurita Constituents - Ninon G. E. R. Etsassala; Jelili A. Badmus; Jeanine L. Marnewick; Emmanuel I. Iwuoha; Felix Nchu; Ahmed A. Hussein (MDPI AG, 2020)
Diabetes mellitus (DM) is one of the most dangerous metabolic diseases with a high rate of mortality worldwide. It is well known that insulin resistance and deficiency in insulin production from pancreatic β-cells are the main characteristics of DM. Due to the detrimental side effects of the current treatment, there is a considerable need to develop new effective antidiabetic drugs, especially alpha-glucosidase and alpha-amylase inhibitors with lesser adverse effects. These inhibitors are known to be directly involved in the delay of carbohydrate digestion, resulting in a reduction of glucose absorption rate and, consequently, reducing the postprandial rise of plasma glucose, which can reduce the risk of long-term diabetes complications. Furthermore, natural products are well-known sources for the discovery of new bioactive compounds that can serve as scaffolds for drug discovery, including that of new antidiabetic drugs. The phytochemical investigation of Salvia aurita collected from Hogobach Pass, Eastern Cape Province, South Africa (SA), yielded four known abietane diterpenes namely carnosol (1), rosmanol (2), 7-methoxyrosmanol (3), 12-methoxycarnosic acid (4), and one flavonoid named 4,7-dimethylapigenin (5). Structural characterization of these isolated compounds was conducted using 1 and 2D NMR, in comparison with reported spectroscopic data. These compounds are reported for the first time from S. aurita. The biological evaluation of the isolated compound against alpha-glucosidase exhibited strong inhibitory activities for 3 and 2 with the half maximal inhibitory concentration (IC50) values of 4.2 ± 0.7 and 16.4 ± 1.1 µg/mL respectively, while 4 and 1 demonstrated strong alpha-amylase inhibitory activity amongst the isolated compounds with IC50 values of 16.2 ± 0.3 and 19.8 ± 1.4 µg/mL. Molecular docking analysis confirms the strong inhibitory activity of 3 against alpha-glucosidase. Additionally, excellent antioxidant capacities were displayed by 2, 1, and 3, respectively, with oxygen radical absorbance capacity (ORAC) (25.79 ± 0.01; 23.96 ± 0.01; 23.94 ± 0.02) mM Trolox equivalent (TE)/g; 1 and 2 as ferric-ion reducing antioxidant power (FRAP) (3.92 ± 0.002; 1.52 ± 0.002) mM ascorbic acid equivalent (AAE)/g; 5 and 2 as Trolox equivalent absorbance capacity (TEAC) (3.19 ± 0.003; 2.06 ± 0.003) mM TE/g. The methanolic extract of S. aurita is a rich source of abietane diterpenes with excellent antioxidant and antidiabetic activities that can be useful to modulate oxidative stress and might possibly be excellent candidates for the management of diabetes. This is the first scientific report on the phytochemical isolation and biological evaluation of the alpha-glucosidase and alpha-amylase inhibitory activities of Salvia aurita.